The The Influence of Multimedia Features, Content Features and Picture Features in Online Advertising on Customer Purchase Intention towards Goods or Services - Leong May Li; Ng Jeng Wah (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
This study investigates online advertising related relationships among multimedia features (MF), content features (CF) and picture features (PF) towards customer purchase intention (CPI) of goods or services. An online questionnaire is distributed to 200 respondents for collecting data. SPSS Statistic System is used to analysis the research data including descriptive analysis, reliability test, Pearson correlation coefficient and multiple linear regression. Analysis results show that MF, CF, and PF have a positive relationship toward customer purchase intention. There are some limitations of this study and recommendations for future researchers are stated in the report. Therefore, solutions to enhance the problems is provided for future researchers.